The Effect Of Using Kahoot Media In Improving Students' Motivation And Learning Outcomes In The Economics Subject Of Grade XI - Purba, Friska Patrecia; Siahaan, Mian; Siahaan, Nova Yunita Sari (STABN RADEN WIJAYA WONOGIRI, 2023)
The low motivation and unsatisfactory learning outcomes of students in economics subjects have encouraged the need for innovative teaching approaches that integrate technology into the classroom. This study aimed to analyze the effect of Kahoot!, a game-based learning platform, on students' learning motivation and academic achievement in economics at SMA Swasta Bandung Percut Sei Tuan in the 2024/2025 academic year. A quantitative method with a quasi-experimental design using a non-equivalent control group was employed, involving 59 students divided into experimental and control classes. Data were collected through tests, questionnaires, and classroom observations, then analyzed using normality tests, homogeneity tests, and independent sample t-tests. The results demonstrated that the use of Kahoot! had a significant positive impact on both motivation and learning outcomes. Students in the experimental class showed substantial improvement, with their average score increasing from 53.33 on the pretest to 82.67 on the posttest, while the control class only improved from 42.76 to 55.07. Moreover, motivation levels in the experimental group increased considerably, as evidenced by higher enthusiasm, stronger engagement, and more active participation during learning activities. These findings suggest that Kahoot! is not only effective in enhancing cognitive achievement but also fosters affective aspects of learning by creating a dynamic, enjoyable, and competitive learning environment. The integration of such interactive digital media can be considered an important strategy for teachers to improve the quality of instruction, particularly in economics subjects that often appear abstract and less engaging for students. Therefore, Kahoot! holds great potential to serve as a complementary tool in modern pedagogy, supporting both immediate academic success and long-term motivation in learning